If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5x = -3x + -93 Reorder the terms: 3 + 5x = -93 + -3x Solving 3 + 5x = -93 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 3 + 5x + 3x = -93 + -3x + 3x Combine like terms: 5x + 3x = 8x 3 + 8x = -93 + -3x + 3x Combine like terms: -3x + 3x = 0 3 + 8x = -93 + 0 3 + 8x = -93 Add '-3' to each side of the equation. 3 + -3 + 8x = -93 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = -93 + -3 8x = -93 + -3 Combine like terms: -93 + -3 = -96 8x = -96 Divide each side by '8'. x = -12 Simplifying x = -12
| 20x+7y=3fory | | 8m-24=4 | | 6x+5=-3x+104 | | -5x+4=68+3x | | -2x+10+7x=65 | | 4+7x+x=68 | | 180=(30+x)+30+9x | | 8.5+x=7.1-x | | 62=y-19 | | x^4-8x^3+24x^2-32x=65 | | 15y-9y= | | -3-y=6 | | (40x)+(100y)=2500000 | | 2x+9=13+2x | | 15-2y/4=3 | | 2.5n-14=-12.25 | | 56-21x=-4x+29 | | 4x-8=9x+3 | | 2x-5x-7=-14 | | x+-10=12 | | -12x+10+17x-7=12+4x-2+x | | P+7=32 | | -4.9x^2-8x-30=0 | | 3a^3b-24b^4=0 | | 6k+3w-w+5k= | | 2.3x=47 | | 3m+5n=6m-2n | | 5(2)+15x=10 | | 21x^2-6x+13=0 | | x^2+9y^2=28 | | 3x+2-x-5=7x+6-4x-2 | | -6(2t+10)=-24 |